Propagation of SH waves in corrugated FGPM layer lying over a piezomagnetic half-space. Issue 1 (2nd January 2019) - Mondal, Sonali; Anand Sahu, Sanjeev
Abstract: Present article aims to study the propagation of horizontally polarized shear waves (SH waves) in Functionally Graded Piezoelectric Material (FGPM) layer. The considered FGPM layer is lying over a piezomagnetic half-space with corrugated interface. The material properties of FGPM layer are assumed to have exponential function distribution along thex -axis. Two cases are considered - electrically and magnetically open case and electrically and magnetically short case. Dispersion relations are obtained in determinant form. Numerical example has been provided for graphical representation of findings. This study provides a theoretical foundation for optimization of Surface Acoustic Wave (SAW) devices.